(untitled) (Research, Society and Development, 2021)
The clinical magnitude of the cases of coinfection by Human Immunodeficiency Virus / tuberculosis requires a great deal of nursing knowledge regarding health care, especially health promotion. In this context, the objective of this study was to identify the strategies used by nursing in the care of HIV/AIDS patients coinfected with tuberculosis. A survey of scientific production was carried out from August 2018 to May 2019, through the electronic search of articles indexed in the following databases: Nursing Database, Latin American and Caribbean Literature in Health Sciences, Library Scientific Electronic Library Online and Database of the State University of Rio de Janeiro. It was considered research that approached the proposed theme, published in Portuguese, in the form of original articles, obeying the publication period between 2013 to 2018, with a final selection of 11 articles. The results showed that the main strategies are to guide the client about the pathology 30% (3), to promote the bond and empathy 29% (2), to guide the importance of the return visit 29% (2) and to train health teams 29 % (2). It is hoped that this study may support the conduction of research that effectively addresses the strategies used by nursing in the care of HIV/AIDS patients co-infected with tuberculosis.